Low carbon optimal operation of integrated energy system based on carbon capture technology, LCA carbon emissions and ladder-type carbon trading - Wang, Rutian; Wen, Xiangyun; Wang, Xiuyun; Fu, Yanbo; Zhang, Yu (Applied energy, 2022)
•Greenhouse gas emissions are analyzed by the life cycle assessment.•Carbon emissions are controlled by the ladder-type carbon trading mechanism.•Economics of carbon capture power plants assessed by economic cost analysis.•A low-carbon economic model of an integrated energy system is established.•The low carbon emission reduction and economic benefits of this model are proved. Facing the problem of the exhaustion of fossil energy and the low-carbon requirements of the power industry, low-carbon technology cooperates with market mechanisms to achieve low-carbon operation of the integrated energy system (IES). This paper establishes an IES considering carbon capture technology (CCT). Life cycle assessment (LCA) analysis the greenhouse gas emissions of different energy chains in IES. The normalized carbon emission coefficient is calculated. The carbon emission coefficient and the reward and punishment ladder-type carbon trading mechanism are used to calculate the carbon trading cost. And the economic benefits of carbon capture power plants are evaluated. Based on the constraints of the system's operating mechanism, with the optimal economic cost as the objective function, a low-carbon economic operating model is established in an integrated energy system that considers carbon capture technology. The model is analyzed through an example. In the example results, the total cost of the model is slightly increased by 3.2%. And the carbon emissions are greatly reduced by 72.66%. It proves that the reasonable planning of the carbon trading market and the transformation of high-carbon power plants can effectively promote the low-carbon development of IES.